Urban Transport in Asia: An Agenda For The 1990s - Peter Midgley (Journal of Regional and City Planning, 1993)
Asia is estimated to have had a total population of 2.9 billion inhabitants in 1990 or half the world's population. The vast majority are concentrated in the 16 countries classified as low"”income economies with GNP per capita below $545 in 1988. This group of countries aiso contains the majority of the region's (and the world's) urban population and the majority of cities with populations in excess of one million.In terms of economic growth, Asia is undoubtedly the most dynamic region in the world today. Notwithstanding the disparities in the economic performance of individual economies, the growth in GNP of the region as a whole has averaged nearly seven percent per annum during the 19805. This compares with world economic growth of around three percent per annum and less than two percent for developing countries. Thus the record for the Asia region is impressive when compared with the world as a whole, and particularly when compared with developing countries in other regions.The impressive performance of Asia in terms of economic development and the growth in population is causing the region to grapple with extremely rapid rates of urbanization. Already, more than hallr of the World's urban population increases occur in Asia and the majority of this growth is occurring in the region's low income countries. It is estimated that by the turn of this century, the urban population in Asia will increase by 420 million from 1.2 to 1.6 billion. The resultant increase in the proportion of urban residents within the total population would be from 39 percent in 1990 to 46 percent by the year 2000.By the year 2000, there is expected to be 13 megacities (cities with populations in excess of 10 million) in Asia with a combined population of 179 million. Within a decade, more than half the world's 21 megacities and just over two thirds of the 18 megacities in the developing world would be located in Asia. And the majority of these would be in low income countries.The extent to which Asian cities meet the challenges of urbanization and contribute to macroeconomic performance will, to a large extent, depend on how efficiently they can transport the goods, services, information and people upon which their economic activities depend.